2011
DOI: 10.1167/iovs.10-6268
|View full text |Cite
|
Sign up to set email alerts
|

LOXL1Promoter Haplotypes Are Associated with Exfoliation Syndrome in a U.S. Caucasian Population

Abstract: LOXL1 promoter haplotypes were identified that are significantly associated with ES/EG in a U.S. Caucasian population. These results suggest that promoter region SNPs can influence LOXL1 gene expression, potentially causing a reduction of enzyme activity that may predispose to disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(35 citation statements)
references
References 27 publications
2
33
0
Order By: Relevance
“…This sequencing effort confirmed previously reported strong allele reversals at key LOXL1 common variants and also at recently reported non-coding variants (Supplementary Tables 3, 4 and 5) 13,21,23 .…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…This sequencing effort confirmed previously reported strong allele reversals at key LOXL1 common variants and also at recently reported non-coding variants (Supplementary Tables 3, 4 and 5) 13,21,23 .…”
Section: Resultssupporting
confidence: 89%
“…Realizing that large and inclusive international collaborative efforts are essential in providing new biological leads in complex disease pathogenesis [15][16][17][18][19][20] , we report here a world-wide collaborative XFS study aimed at further understanding the genetic basis of the disorder. Firstly, due to the allele reversals seen at LOXL1 common polymorphisms led by rs3825942 G>A (p.153Gly>Asp) and to a lesser extent, rs1048661 T>G (p.141Leu>Arg) 12,[21][22][23][24][25][26][27][28] (Supplementary Figure 1), we aimed to refine the LOXL1 genetic landscape by performing deep sequencing of the entire gene in 5,570 XFS and XFG cases and 6,279 controls from 9 countries (Supplementary Table 1). The previously reported CACNA1A locus was also sequenced to assess if rare non-synonymous amino acid substitutions within the gene could provide further insights [29][30][31] .…”
Section: Introductionmentioning
confidence: 99%
“…In a population-based screening study in Norway, the overall prevalence of OAG was found to be 8.3%, with approximately 30% of the population with exfoliation syndrome having EG. 60 Exfoliation syndrome has since been described in multiple ethnicities and races around the world, including populations in the United States, 61,62 Iran, 63 Australia, 64 South Africa, 65 China, 66 India, 67 Sweden, 68 Jordan, 69 Japan, 70 Sri Lanka, 71 Spain, 72 Congo, 73 and Nigeria. 74 The Reykjavik Eye Study examined the prevalence and 5-year incidence of exfoliation syndrome in 1045 Icelanders over the age of 50 years.…”
Section: Open Angle Glaucomamentioning
confidence: 99%
“…Functional variants could include those in coding and/or noncoding regions. To identify variants associated with disease risk, haplotype analysis using variants distributed throughout the LOXL1 regulatory regions and gene coding regions identified a risk haplotype in a Caucasian population from the United States that included a LOXL1 promoter region variant previously shown to reduce gene expression (rs16958477) [6,7]. These variants and other regulatory elements that could influence LOXL1 expression are shown in Figure 2.…”
mentioning
confidence: 99%